FROM PHYSIOLOGICAL TO PATHOLOGICAL METEOSENSITIVITY - Yabluchanskiy, M. I.; Bychkova, O. Y.; Lysenko, N. V.; Makienko, N. V.; MartimyanovaL. О.; Yabluchanskiy, A. M. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
This paper is dedicated to the problem of physiological and pathological meteosensitivity (meteodependency or meteopathy).We introduce and discuss the definition for individual meteodependency, define factors, mechanisms, clinical signs, diagnosis, and approaches to prophylaxy and treatment of individual pathological meteosensitivity.